Glacier fluctuations in the Northern and Southern Patagonian Ice Fields retrieved from observations on the International Space Station - V. M. Kotlyakov (Lëd i Sneg, 2020)
Quantitative indicators of changes in 37 glaciers of the Patagonian Northern and Southern glacial fields were determined by means of decoding and analysis of photographs obtained by astronauts from the Russian segment of the International Space Station. On the basis of this information it was concluded that in 2002–2016 the glaciers of both fields of Patagonia continued to retreat. The frontal parts of the nine glaciers retained their positions, while others reduced at an average rate of several dozen up to 430 m/year. Repeated monitoring of 16 glaciers from this selection and analysis of the data obtained in 2016–2019 confirm this conclusion. The only exception was the O’Higgins Glacier, which did not change position of its frontal part for 12 years and then retreated in 2018–2019 to 1,250 m. In some cases, a gradual decrease in area of the frontal part of the glacier was accompanied by a sharp collapse of the lower zone with the formation of extensive fields of icebergs. The dynamics of the Bruggen Glacier (Pius XI) are not typical for the region under consideration: for many years this glacier has been advancing. This development cannot be explained without detailed field investigation in the area of snow and ice accumulation of the glacier. Perhaps that was due to a snow-drift transport in an extensive area of accumulation that supported the preservation of the size of the glacier tongue, and even its advance. According to our observations, the average rate of retreat of the glaciers of the Western and Eastern slopes of the Southern Ice Field significantly decreased since 2010, i.e. their degradation slowed down. At the same time, glaciers of the Northern Ice Field continued to decrease intensively.